2003
DOI: 10.1145/636865.636867
|View full text |Cite
|
Sign up to set email alerts
|

Time-space trade-off lower bounds for randomized computation of decision problems

Abstract: We prove the first time-space lower bound trade-offs for randomized computation of decision problems. The bounds hold even in the case that the computation is allowed to have arbitrary probability of error on a small fraction of inputs. Our techniques are extension of those used by Ajtai and by Beame, Jayram, and Saks that applied to deterministic branching programs. Our results also give a quantitative improvement over the previous results.Previous time-space trade-off results for decision problems can be div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 31 publications
0
44
0
Order By: Relevance
“…The following is a generalization of an argument of Babai, Frankl, and Simon [2]. Its appears in a somewhat different form in [4]. Let k = p n/m.…”
Section: Lower Bounds For Set Disjoint-ness and Other Problemsmentioning
confidence: 96%
See 1 more Smart Citation
“…The following is a generalization of an argument of Babai, Frankl, and Simon [2]. Its appears in a somewhat different form in [4]. Let k = p n/m.…”
Section: Lower Bounds For Set Disjoint-ness and Other Problemsmentioning
confidence: 96%
“…[4]) could be used to obtain tradeoffs between reversals and space in the read/write stream model by bounding the time used as a function of the number of reversals. However, those lower bounds only apply with readonly inputs and sub-linear space bounds; with the ability of read/write stream algorithms to write to linear (or even significantly super-linear) numbers of memory locations on the external tapes, neither the time nor the space bounds are small enough for the time-space tradeoffs to apply.…”
Section: Introductionmentioning
confidence: 99%
“…We should point out that Beame et al [BSSV03], building on earlier work by Ajtai [Ajt99], establish nonuniform time-space lower bounds for a problem in P based on binary quadratic forms. They show that any branching program for that problem that uses only space n 1−ǫ for some positive constant ǫ takes time Ω(n · log n/ log log n),…”
Section: Further Researchmentioning
confidence: 94%
“…We point out that some of the more recent work in circuit complexity does not seem to have implications for satisfiability. In particular, the non-uniform time-space lower bounds by Ajtai [Ajt99] and their improvements by Beame et al [BSSV03] do not yield time-space lower bounds for satisfiability. These authors consider a problem in P based on a binary quadratic form, and showed that any branching program for it that uses only n 1−ǫ space for some positive constant ǫ takes time Ω(n · log n/ log log n).…”
Section: Scopementioning
confidence: 97%